Distinctiveness And Potentials Of Two Flowering Roadside Hedgerows, Turnera Ulmifolia And Melastoma Malabathricum As Benefecial Plants For Iinsects - Nur Athirah Abdullah; Faszly Rahim (Zibeline International Publishing, 2024)
Beneficial flowering plants play a vital role in attracting beneficial insects such as parasitoid that controls insect pests. In order to evaluate the effectiveness of two species of flowering plants as beneficial hedgerow plants, we identify insects communities of T. ulmifolia and M. malabathricum, which generally grown on roadside. We also compared the insects community of both plants based on time of the day. A total of 5,029 insect individuals were collected through three sampling occasions from five sampling stations of T. ulmifolia and five sampling stations of M. malabathricum. Chi-square test showed that there was a significant difference (χ2=37.3848, df=1, P<0.05) between the composition of insect communities on M. malabathricum and T. ulmifolia. The insect visiting M. malabathricum were similar at both night and day while T. ulmifolia attracted different insect community depending on the time of the day. The results suggested that different plant species would attract a different community of insects. T. ulmifolia success in attracting the visitation of beneficial insect but its effectiveness is limited to a short period of time. Meanwhile, the effectiveness of M. malabathricum as beneficial plant is yet illuminated.